2020
DOI: 10.1021/acs.est.0c02949
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Capture the Spatial and Temporal Heterogeneity of Aquatic Plant Iron Root Plaque In Situ

Abstract: The roots of aquatic plants, including rice, release oxygen into the subsurface, precipitating reduced metals, such as iron (Fe) and manganese (Mn), as plaques that form on the surface of the roots. These plaques are a unique habitat for microorganisms and a hotspot for biogeochemical cycling, including the toxic trace metalloid arsenic (As). However, studying plaque deposition and mineral composition in this spatially and temporally heterogeneous environment is challenging, particularly in situ. Here, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Previous studies have commonly used X-ray powder diffractometry (XRD), X-ray absorption near edge structure (XANES), X-ray fluorescence spectrometry (XRF), and X-ray photoelectron spectroscopy (XPS) to characterize the structure and composition of iron plaque. It was reported that the primary constituent of iron plaque was ferrihydrite, in addition to small amounts of goethite, lepidocrocite, and siderite. In comparison, Mössbauer spectra could help to obtain comprehensive information including the crystalline, weakly crystalline state, and valence of Fe-based materials. , Mössbauer spectra results in our study indicated that the iron plaque mainly consisted of phyllosilicates-Fe­(II) (20.3%) and Fe­(OH) 3 (79.7%) (Figures c and Table S3). The absence of well-defined sextets suggested that the iron plaque contained little or no pure particles of crystalline iron oxides such as goethite, hematite, and magnetite/maghemite .…”
Section: Resultssupporting
confidence: 48%
“…Previous studies have commonly used X-ray powder diffractometry (XRD), X-ray absorption near edge structure (XANES), X-ray fluorescence spectrometry (XRF), and X-ray photoelectron spectroscopy (XPS) to characterize the structure and composition of iron plaque. It was reported that the primary constituent of iron plaque was ferrihydrite, in addition to small amounts of goethite, lepidocrocite, and siderite. In comparison, Mössbauer spectra could help to obtain comprehensive information including the crystalline, weakly crystalline state, and valence of Fe-based materials. , Mössbauer spectra results in our study indicated that the iron plaque mainly consisted of phyllosilicates-Fe­(II) (20.3%) and Fe­(OH) 3 (79.7%) (Figures c and Table S3). The absence of well-defined sextets suggested that the iron plaque contained little or no pure particles of crystalline iron oxides such as goethite, hematite, and magnetite/maghemite .…”
Section: Resultssupporting
confidence: 48%
“…Short-range ordered Fe oxides have been observed on Mn IRIS in a soil subjected to three different temperatures; however, Fe deposits only appeared at the water table and after the Mn was removed, suggesting oxidation of Fe­(II) by oxygen . Fe oxides have also been found on uncoated IRIS films adjacent to rice rhizospheres, resulting in root-shaped Fe oxide deposits due to the oxidation of Fe­(II) by root radial oxygen loss. , …”
Section: Introductionmentioning
confidence: 97%
“…20 Fe oxides have also been found on uncoated IRIS films adjacent to rice rhizospheres, resulting in root-shaped Fe oxide deposits due to the oxidation of Fe(II) by root radial oxygen loss. 25,26 Past work has established that deposition of neoformed Fe oxides on Mn IRIS films varies between and within soils, and variations in colors formed on the IRIS film after deployment suggest that complex geochemistry occurs on the surface. It is crucial to better understand the fate of Mn and Fe on IRIS films when used as passive sensors of reducing conditions and as possible samplers of associated trace elements.…”
Section: ■ Introductionmentioning
confidence: 99%